HARMONIZATION OF FOSTER’S POLITICAL ECOLOGY AND ISLAMIC THOUGHT: A STRUCTURAL SPIRITUAL APPROACH TO INDONESIA’S ENVIRONMENTAL CRISIS - Afif Kholidin; Khoirul Fathoni; Ali Musyafak; Saifudin Zuhri; Ida Nur Lailatul Kodriyah; Fathul Mufid (UIN Antasari Banjarmasin, 2025)
This article proposes an interdisciplinary framework that bridges Marxist political ecology and Islamic ethics to address ecological injustice in Muslim-majority contexts. Existing scholarship reveals a critical research gap: while political ecology particularly John Bellamy Fosterâ€™s theory of the metabolic rift diagnoses capitalism as the systemic driver of ecological degradation, it often overlooks the spiritual and ethical dimensions of human nature relations. Conversely, Islamic environmental thought emphasizes the theological values of stewardship (khalÄ«fah), justice (â€˜adl), and balance (mÄ«zÄn), yet tends to lack a rigorous structural critique of capitalist modes of production and consumption. To overcome this epistemic divide, the study synthesizes these two perspectives into a hybrid model of ecological justice that is both structurally critical and spiritually grounded. Theoretically, it advances political ecology by reintroducing religion not merely as moral discourse but as an analytical category capable of shaping socio-ecological critique. Practically, it outlines four domains of implementation: (1) ecological justice policies through environmental zakat and waqf; (2) integration of eco-ethical principles into Islamic education; (3) mosque-centered community empowerment; and (4) the adoption of green technologies aligned with sustainability (istidÄmah). This integrated framework enriches global sustainability debates by offering a non-secular paradigm rooted in Islamic ethical thought, while positioning Indonesia as a potential model for environmentally responsible Muslim societies that combine structural reform with moral transformation.